1991
DOI: 10.1016/0272-6963(91)90072-6
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and marketing interdependence in the new venture firm: An empirical study

Abstract: This research addresses the interdependent nature of manufacturing and marketing decisions in new venture firms. Based on an empirical study of new venture firms in the communications and computer equipment manufacturing industry, the research first shows that the perception of key aspects of the environment, entry barriers, and hostility does not differ between successful and unsuccessful new venture firms. Such a finding suggests that new venture success is based on much more than an accurate perception of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
(29 reference statements)
1
16
0
2
Order By: Relevance
“…Anatan (2006) menyebutkan bahwa sumber keunggulan kompetitif perusahaan dapat ditemukan melalui kemampuan manajemen dalam mengkonsolidasikan kompetensi bidang fungsional perusahaan, yaitu kompetensi pemasaran, inovasi serta bidang operasi. Studi terintegrasi dilakukan oleh Deane et al (1991) yang mengkaitkan antara produksi dan pemasaran. Simpulan studi tersebut ialah bahwa strategi operasi dan pemasaran merupakan prediktor terbaik kesuksessan perusahaan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Anatan (2006) menyebutkan bahwa sumber keunggulan kompetitif perusahaan dapat ditemukan melalui kemampuan manajemen dalam mengkonsolidasikan kompetensi bidang fungsional perusahaan, yaitu kompetensi pemasaran, inovasi serta bidang operasi. Studi terintegrasi dilakukan oleh Deane et al (1991) yang mengkaitkan antara produksi dan pemasaran. Simpulan studi tersebut ialah bahwa strategi operasi dan pemasaran merupakan prediktor terbaik kesuksessan perusahaan.…”
Section: Pendahuluanunclassified
“…Balasubramanian dan Bhardwarj (1999) menyatakan dimana perusahaan yang mempunyai kerja sama yang baik antara manajemen pemasaran dan operasi akan lebih bersaing dibandingkan perusahaan yang mempunyai konflik pada kedua bidang tersebut. Studi terintegrasi dilakukan oleh Deane et al (1991) yang mengkaitkan antara produksi dan pemasaran. Simpulan studi tersebut ialah bahwa strategi operasi dan pemasaran merupakan prediktor terbaik kesuksesan perusahaan.…”
Section: Pengintegrasian Pemasaran Dan Operasi Pada Supply Chain Manaunclassified
“…They found that the majority of the proposed relationships were positive except when there were cases of low uncertainty. Similarly Deane, McDougall, and Gargeya (1991) found that while operations or marketing decisions are not sufficient by themselves to predict success of new venture firms, together these decisions can moderately predict success. O' Leary-Kelly and Flores (2002) also found that the impact of the integration of manufacturing and marketing/sales decision on organizational performance is moderated by a firm's business strategy and demand uncertainty.…”
Section: Empirical Papersmentioning
confidence: 99%
“…In the High Labour Intensity LEC scrviccs \Ve find the classic Profcssional Services such as Physicians, Lawyers, Accountants or Architects, while the same costs structurc with SEC gives us as rcsult Travel Agencies and Fairs, Expositions or Confcrcncc Arranger scrviccs. Figure 2b [23] have demonstrated that variables reflecting the interdependcncy of manufacturing/service and marketing strategics are the best predietor of firm sucecss. Other researches, like Heskett el al.…”
Section: Customisation and Scrvicc Opcrations Managcmcntmentioning
confidence: 99%
“…have mueh to do with the finn's compctitive advantages [23]. Strategie assessment, including the external and internal analyses wil!…”
Section: Customisation and Its Timc-bascd Cffccts: The Lec-sec Matrixmentioning
confidence: 99%